MILCOM 2013 - 2013 IEEE Military Communications Conference 2013
DOI: 10.1109/milcom.2013.179
|View full text |Cite
|
Sign up to set email alerts
|

On the Exploitation of the Android OS for the Design of a Wireless Mesh Network Testbed

Abstract: Wireless devices running the Android operating system offer a novel opportunity to study network behaviors and to observe and modify in real time key networking parameters. This opens up an unprecedented opportunity to study, test and evaluate the performance of techniques operating at different layers of the protocol stack and adopting the cognitive networking paradigm. In this paper, we describe our novel IEEE 802.11 mesh network testbed that integrates Android based devices. The aim is to build a flexible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Through a simulation campaign, for the case of a linear topology, we have shown that our approach can significantly outperform the standard TCP with OLSR protocol both in a static and in a mobile scenario, in terms of increased average throughput and decreased outage probability. In our future work, we plan to address more general topologies, and implement this framework in our mobile network testbed [29], in order to study its performance in realistic wireless scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Through a simulation campaign, for the case of a linear topology, we have shown that our approach can significantly outperform the standard TCP with OLSR protocol both in a static and in a mobile scenario, in terms of increased average throughput and decreased outage probability. In our future work, we plan to address more general topologies, and implement this framework in our mobile network testbed [29], in order to study its performance in realistic wireless scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Even though Serval targets commercially available devices, it appears that in order to perform multi-hop communication, the Linux kernel code of the Android platform must be modified. Indeed, it is not possible to create an efficient multi-hop network among devices with the standard Wi-Fi Direct available on off-the-shelf Android devices as the routing can be implemented only as an application over the transport layer [8]. In a nutshell, Android offers a Wi-Fi Direct interface for one hop ad hoc networking.…”
Section: Practical Middleware Solutionsmentioning
confidence: 99%
“…This approach is used in [9] where the authors utilize the Click software architecture to implement and test a novel scheduling algorithm for 802.11 that prevents nodes experiencing poor channel conditions from monopolizing the wireless medium. In [10], the authors modify the Linux kernel in an Android device to enable the IBSS (or ad-hoc) mode. The authors also create sockets between the kernel space and the user space to monitor the link quality conditions and check the stability and the performance of the IBSS network.…”
Section: Experimental Wireless Researchmentioning
confidence: 99%